PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI, MOTIVASI TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN PADA DINAS PEMERINTAHANAN DESA KABUPATEN LUMAJANG (PEMDES) - Dihan Profita (Jurnal Bisnis dan Manajemen, 2017)
The background of this reasearch is that there is effort from enterprises/companies to improve their employees’ performance as an objective of an enterprise/company. Performance strongly depends on the awareness of each employee. In order to improve the employees’ performance, the enterprise/company is required to maintain the establishment of human resource, by doing, for example, improving the efectiveness and efficiency so that employees feel satisfied, resulting improvement in employees’ performance. This research also uses analysis unit consisting of the employees of PEMDES service in Lumajang district with the employees’ population of 80 people and uses path analysis method as data analysis technique.According to the result and discussion, this research’s conclusions can be explained as the following: 1) leadership influences work satisfaction; 2) organization’s culture influences work satisfaction; 3) motivation influences work satisfaction; 4) leadership influences employees’ performance; 5) organization’s culture influences employees’ performance; 6) motivation influences employees’ performance; 7) work satisfaction influences employees’ performance, 8) leadership indirectly influences employee’s performance through work satisfaction; 9) organization’s culture indirectly influences employee’s performance through work satisfaction; and 10) motivation indirectly influences employee’s performance through work satisfaction at PEMDES service of Lumajang district. DOI : https://doi.org/10.26905/jbm.v4i2.1696